TRANSFORMASI PERAN AKUNTANSI BIAYA LINGKUNGAN DALAM PERUSAHAAN - Mursalin - (Universitas PGRI Palembang, 2008)
The view of environmental cost which reflect company responsibility has changed. In conventional views, environmental cost is a part of expenses that reduce the company profit and cause the poor competition. Those views were driven by assumption that as expense, environmental cost doesn’t impact product values. Using life cycle cost approach in Total Environmental Quality Management (TEQM), that adopted from Total Quality Management (TQM), the orientation of environmental cost has changed to be investment and important factors to gain the competitive advantage. In the conventional views, environmental cost is considered as recovery cost or conservation cost. In modern views, it has transformed to be strategic decision variable both in clean product investment and using of raw material that have minimum waste. In the production process based on the systematic cause effect analysis and flow of materials, environmental cost accounting information are possible to identify the source of inefficient process and source of residual waste. They cause higher cost of production on the one hand, and lower quality and product values, on the other hand. Therefore, the integration of environmental cost accounting since the beginning of product creation, for example in design product process and product design phase, can reduce the waste and other inefficient activities. It means production process can reduce the cost of product, that simultaneously can increase the quality and product values. The company will be able to eliminate or even diminish all products and processes waste, since early stages of production process that have been done (zero damage). Keywords : Evironmental Cost, Total Environmental Quality Management